2018
DOI: 10.1111/maec.12501
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of microzooplankton in the central Arabian Sea during spring intermonsoon

Abstract: Spatial variability of microzooplankton (MZP; organisms in size 20–200 μm) along with total heterotrophic bacteria (THB) and picophytoplankton in the upper 120‐m water column of the central Arabian Sea (AS) was studied during the spring intermonsoon period (March 2015). Six stations divided into three regions (northern, southern, and central) were sampled along 68°E transect, between 9°N and 21°N. A total of 25 species of MZP were recorded corresponding to loricate ciliates (11 species), aloricate ciliates (tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The overall latitudinal distribution of isoprene shows a decreasing trend from the highly productive northern regions to the less productive southern Arabian Sea. The latitudinal distribution of isoprene is consistent with microzooplankton (MZP) biomass which showed higher counts (8–9 × 10 3 org./m 3 ) in the northern and lower counts (7–8 × 10 3 org./m 3 ) in the central Arabian Sea during the inter-monsoon period . Madhupratap et al (1996) reported the higher bacterial productions and MZP biomass during inter-monsoon compared to the northeast monsoon over the Arabian Sea during the US Joint Global Ocean Flux Study (JGOFS) program.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…The overall latitudinal distribution of isoprene shows a decreasing trend from the highly productive northern regions to the less productive southern Arabian Sea. The latitudinal distribution of isoprene is consistent with microzooplankton (MZP) biomass which showed higher counts (8–9 × 10 3 org./m 3 ) in the northern and lower counts (7–8 × 10 3 org./m 3 ) in the central Arabian Sea during the inter-monsoon period . Madhupratap et al (1996) reported the higher bacterial productions and MZP biomass during inter-monsoon compared to the northeast monsoon over the Arabian Sea during the US Joint Global Ocean Flux Study (JGOFS) program.…”
Section: Resultsmentioning
confidence: 63%
“…The latitudinal distribution of isoprene is consistent with microzooplankton (MZP) biomass which showed higher counts (8−9 × 10 3 org./m 3 ) in the northern and lower counts (7−8 × 10 3 org./m 3 ) in the central Arabian Sea during the inter-monsoon period. 44 Nutrients are enriched at the surface because of strong vertical mixing in winter season, resulting in enhanced biological production during inter-monsoon. 46 The high surface marine productivity even after a pause in seasonal deeper water upwelling is referred to as the "Arabian Sea Paradox".…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation